(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The purpose of this research is to determine the level of acceptance among cocoa farmers in the La Cadena sector of the Valencia canton, province of Los Ríos, of a proposal for associativity. For this purpose, surveys were conducted to 25 cocoa farmers in the study area, aimed at identifying the main reasons that farmers have to associate, quantify the degree of acceptance of the associativity proposal, determine associativity strategies for the improvement of the production chain of the sector La Cadena, canton Valencia, province of Los Rios. The main results showed that in the area there is a great willingness to associate, so that 88.00% indicated that they would associate, rating the associativity plan as important (36.00%) and very important (52.00%), considering that it is of greater importance to acquire associative credits. Farmers preferably aim to improve marketing, access to new production technologies and markets with better prices. The objectives that farmers seek to associate are new markets for the sale of cocoa, elimination of intermediaries and post-harvest management of the bean. The associative strategies that farmers are inclined to use are to attend different production fairs in which they participate with their product in search of potential markets.